BRCA1 and MAD2 Are Coexpressed and Are Prognostic Indicators in Tubo-ovarian High-Grade Serous Carcinoma. Issue 3 (March 2018) - Byrne, Tara; Nelson, Laura; Beirne, James P.; Sharpe, Daniel; Quinn, Jennifer E.; McCluggage, W. Glenn; Robson, Tracy; Furlong, Fiona
Abstract : Objectives: The aim of this study was to investigate the relationship between BRCA1 and mitotic arrest deficiency protein 2 (MAD2) protein expression, as determined by immunohistochemistry, and clinical outcomes in epithelial ovarian carcinoma (EOC). Methods: A tissue microarray consisting of 94 formalin-fixed paraffin-embedded EOC with fully matched clinicopathological data were immunohistochemically stained with anti-BRCA1 and anti-MAD2 antibodies. The cores were scored in a semiquantitative manner evaluating nuclear staining intensity and extent. Coexpression of BRCA1 and MAD2 was evaluated, and patient survival analyses were undertaken. Results: Coexpression of BRCA1 and MAD2 was assessed in 94 EOC samples, and survival analysis was performed on 65 high-grade serous carcinomas (HGSCs). There was a significant positive correlation between BRCA1 and MAD2 expression in this patient cohort ( P < 0.0001). Both low BRCA1 and low MAD2 are independently associated with overall survival because of HGSC. Low coexpression of BRCA1 and MAD2 was also significantly associated with overall survival and was driven by BRCA1 expression. Conclusion: BRCA1 and MAD2 expressions are strongly correlated in EOC, but BRCA1 expression remains the stronger prognostic factor in HGSC. Abstract : Supplemental digital content is available in the text.